Transferring Non-Responsibility - Pedro Merlussi; Gabriel de Andrade Maruchi (Ethic@: an International Journal for Moral Philosophy)
The Direct Argument argues for the claim that determinism and moral responsibility are incompatible. The most controversial assumption of the argument is the thought that "not being responsible for" transfers across conditionals: if no one is (even partially) morally responsible for the fact that p is true, and no one is (even partially) morally responsible for the fact that p ? q is true, then no one is (even partially) morally responsible for the fact that q is true. Here we argue that the principle is true if one accepts a truth-maker account of the relationship between non-responsibility and propositions. While non-responsibility transfers across conditionals, one upshot of the truth-maker account is that it allows one to be responsible for necessary truths.